Shield Cutting Pile-Group Implementation Effects on the Superstructure. (27th September 2022) - Zhang, Chi; Ma, Shiju; Guo, Yuancheng; Li, Mingyu; Fu, Kui
Abstract : The shield tunneling method is widely used in urban subway construction. However, as the layer stress state changes during shield tunnel construction, layer displacement and surface deformation occur accordingly. This study tries to investigate the settlement and deformation of the masonry structure in shield cutting the composite foundation of group piles in a shield tunnel project at Zhengzhou Metro Line 5. To understand the distribution characteristics and changing rules of building settlement during the process of shield cutting group piles composite foundation passing through the masonry structure, a thorough analysis of the ground surface settlement and building settlement, including on-site measured, was conducted. The results show that piles go down through a composite foundation during shield cutting. The cumulative maximum settlement and maximum differential settlement of the masonry structure were concentrated at the intersection of the tunnel axis and the building. The longitudinal distribution of the cumulative settlement of the south and north wall of the masonry structure changes continuously with the change of the position of the shield excavation surface. That behavior may cause the building to be tilted and deformed and cause the structure to undergo rigid rotation and twisting deformation. Based on the composite pile foundation project of the Shield Tunnel Cutting Group in a specific section of Zhengzhou Metro Line 5, this paper analyzes the surface settlement and foundation settlement data of the building caused by the construction of the shield. It obtains the changes of the surface settlement and the settlement of the foundation of the building. No other changes have been made to the existing cracks in the external walls of the building. At the same time, because of the low angle between the longitudinal axis of the masonry structure and the tunnel axis (22°) and the positive effect of the ring beam and column of the structure in the building, it is clear that the construction of this project has little effect on the upper building, thus showing improved control.